2018
DOI: 10.1007/s10902-017-9954-y
|View full text |Cite|
|
Sign up to set email alerts
|

Servant Leadership and Goal Attainment Through Meaningful Life and Vitality: A Diary Study

Abstract: Despite the emphasis of servant leadership theory on the attention provided to workers' needs and goals, there is a lack of empirical knowledge on the relationship between servant leadership and employees' goal attainment. We provide a theoretical model of the mechanism by which this strong focus of servant leadership on a worker's individual development positively influences the worker's goal attainment. Through a diary study with 126 workers over five consecutive working days, the results indicated a positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 84 publications
1
32
0
2
Order By: Relevance
“…Mental health care workers who experienced high levels of EWB also reported higher levels of task performance, innovative work behavior, and work engagement. In line with other findings [54], this study suggests a spill-over effect of work-related relational and contextual factors influencing domain-free EWB, which spirals back into positive effects within the work domain, particularly in the form of work engagement and task performance. This provides further evidence for the value of enhancing domain-free EWB within a work context as it not only benefits work-related outcomes, such as performance and work engagement, but it also contributes to the societal benefit by, alongside hedonic well-being, enhancing eudaimonic components of full functioning, psychological well-being across domains [78].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Mental health care workers who experienced high levels of EWB also reported higher levels of task performance, innovative work behavior, and work engagement. In line with other findings [54], this study suggests a spill-over effect of work-related relational and contextual factors influencing domain-free EWB, which spirals back into positive effects within the work domain, particularly in the form of work engagement and task performance. This provides further evidence for the value of enhancing domain-free EWB within a work context as it not only benefits work-related outcomes, such as performance and work engagement, but it also contributes to the societal benefit by, alongside hedonic well-being, enhancing eudaimonic components of full functioning, psychological well-being across domains [78].…”
Section: Discussionsupporting
confidence: 90%
“…In a work setting, leadership could be seen as a resource falling in the category of contextual social support. The positive relationship between perceived supervisor support [51], transformational leadership [52], leader's spiritual values [53], and EWB suggests that leaders who model serving behaviors, meaningful work, and the use of individual strengths [54] could shape EWB for health care workers. Servant leadership is recognized as a leadership style which benefits organizations, and society, through its focus on valuing, developing, and engaging employees in an authentic way [55].…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…This effort extends previous studies that have shown mediating influences played by motivational [ 22 , 23 , 24 ], cognitive [ 25 , 26 ], and identification-based mechanisms [ 13 ]. Secondly, the boundary conditions about servant leadership largely focus on employee-centered moderators [ 23 , 27 , 28 ] or organization-centered moderators [ 29 , 30 , 31 ]. This study focuses on LMX to shed light on the leader–follower relationship as a potential moderator.…”
Section: Introductionmentioning
confidence: 99%
“…Employee vitality has received considerable attention in researching the influence of leadership styles and employee outcomes, especially the impact of servant leadership [15,40]. It can be generally defined as an affective component of thriving that refers to individuals' positive and affective feelings of energy, aliveness, and function [13].…”
Section: Vitality As a Mediatormentioning
confidence: 99%